Systems and Training Requirements for Criminal Justice Participants (PROJECT STAR), 1971-1974: California, Michigan, New Jersey, Texas ([Verlag nicht ermittelbar], 1985)
Project STAR was designed to collect information about the various roles of operational criminal justice personnel in order to assist in the design of educational and training programs for these personnel. Data were collected from a two-part questionnaire administered to criminal justice personnel in four states: California, Michigan, New Jersey, and Texas. The first part of the questionnaire contained personal, attitudinal, and opinion items as well as questions concerning the goals of the criminal justice system. The second part presented 97 situations that the respondent was asked to rank using a five-part scale. The situations dealt with the roles of police officers, prosecuting attorneys, defense attorneys, judges, probation officers, correctional officers, and parole officers. Demographic information about the respondents includes age, sex, race, educational attainment, occupation and employing agency, and income.